Clinical Spectrum of Neuritis Optic Patients Receiving Intravenous Corticosteroid Treatments in Doctor Kariadi Hospital Semarang - Gadis Sativa; Riski Prihatningtias (The Indonesian Ophthalmologists Association (IOA, Perhimpunan Dokter Spesialis Mata Indonesia (Perdami)), 2021)
Introduction and Objective: Optic neuritis is inflammation of the optic nerve leading to sudden loss of vision that takes place over several hours or days. Corticosteroids have been widely used in the treatment of optic neuritis due to their anti-inflammatory effects. This study aimed to retrospectively review cases of optic neuritis that have been the administration of intravenous corticosteroid treatment on visual acuity. Methods: The authors conducted a retrospective study of patients who underwent 3 days of intravenous corticosteroid therapy for neuritis optic from January 2018 to December 2018 in Kariadi Hospital. The data collected included patient demographics, onset, clinical examinations, and visual acuity. Result: The authors included 22 eyes from 16 patients who received intravenous corticosteroid treatment for 3 consecutive days during the study period. The study found a mean age of 32,91±9,32 years (18-49 years). The mean onset was 2,36±3,07 months (0,1-12 months). Ten eyes (45,5%) had positive RAPD and five eyes (22,7%) had ocular movement pain. Thirteen patients (59,1%) had papil edema in funduscopy examination. Fourteen eyes (63,6%) had visual acuity at or below 6/60 at the time of presentation. The mean visual acuity at the time of presentation was 2,45±1,79 LogMar units (Range 0,2-5,0 LogMar units). After three days of intravenous corticosteroid treatment, the mean visual acuity was 1,81±1,42 LogMar units (Range 0,1-5,0 LogMar units). The visual acuity before and after treatment were analyzed using the Wilcoxon test and gave p=0,004 as result. Conclusion: Treatment of intravenous corticosteroid commonly gave a better visual acuity on neuritis optic patients. There are no significant differences of onset and clinical examinations in intravenous corticosteroid treatment visual outcome.